La cooperación sur-sur y el posicionamiento del Ecuador como nuevo oferente de ayuda (2008-2015) - García Núñez, Alejandra Vanessa (2016)
Since 2008, Ecuador has gone deep into a complementary way of cooperation that would allow it to establish new types of relations between states of the same level of development, especially the ones located within the region. This type of cooperation is best known as South-South Cooperation, which expresses itself as some of complaint towards the asymmetries of the international system, but seeks to bring cohesion between developing countries in an horizontal and caring way. The objective of the following investigation is to analyze the South-South Cooperation as a mechanism of foreign policy, for promoting regional integration, through the new projects of Ecuador as a new provider of cooperation since 2008 until 2015, which is a period of time that corresponds to a new way of development for Ecuador. In order to achieve this, a theoretical approach of the International Development Cooperation, as well as a report on the state of South- South Cooperation in Ecuador and a mapping of the projects that Ecuador has carried out as a provider of cooperation will be presented.